The Issue of Faith According to Imam Al-Suyuti Through his Book Al-Hawi for Fatwas - Collection and Study - (Islamic Sciences Journal, 2023)
ABSTRACT                   This research, which is entitled: (The issue of faith according to Imam Al-Suyuti through his book Al-Hawi for Fatwas - Collection and Study -) is considered one of the researches that is concerned with the most important issue of the Islamic faith, which is the issue of faith, which was studied by one of the imams of the verifiers of the sunnis and the Group  namely, Imam Al-Suyuti, and the researcher has studied through this research the personal and scientific life of Imam Al-Suyuti, then proceeded to explain the issue of faith in Imam Al-Suyuti, and the scholars’ disagreement in it, and clarifying the most correct ones, then he concluded with the most important results he reached through this research.